2017
DOI: 10.1186/s11671-017-2024-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Deposition Annealing on ZrO2/n-GaN MOS Capacitors with H2O and O3 as the Oxidizers

Abstract: GaN-based metal-oxide-semiconductor capacitors with ZrO2 as the dielectric layer have been prepared by atomic layer deposition. The accumulation and depletion regions can be clearly distinguished when the voltage was swept from −4 to 4 V. Post-annealing results suggested that the capacitance in accumulation region went up gradually as the annealing temperature increased from 300 to 500 °C. A minimum leakage current density of 3 × 10−9 A/cm2 at 1 V was obtained when O3 was used for the growth of ZrO2. Leakage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This result is consistent with the fact that the grain boundaries (as shown in Fig. 4) which are leakage channels [24], increase with the annealing temperature except for the sample annealed at 650°C which does not show a grain structure. In the light of the whole results, it seems that the pH sensitivity is closely related to the level of insulation and/or surface morphology of the dielectric material.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This result is consistent with the fact that the grain boundaries (as shown in Fig. 4) which are leakage channels [24], increase with the annealing temperature except for the sample annealed at 650°C which does not show a grain structure. In the light of the whole results, it seems that the pH sensitivity is closely related to the level of insulation and/or surface morphology of the dielectric material.…”
Section: Resultssupporting
confidence: 89%
“…For all the MIS capacitors, the current density is lower in the positive voltage range. This can be attributed to the formation of a depletion region when the positive voltage is added [24]. The current density increases with the increase of the annealing temperature except for the film annealed at 650°C.…”
Section: Resultsmentioning
confidence: 98%
“…[1][2][3][4] Inserting a dielectric layer in such as MOS structures has been found to result in low leakage currents and high breakdown strengths. Numerous gate dielectrics, including SiN, 2,5) SiO 2 , 3,[6][7][8][9][10] Al 2 O 3 , 4,[11][12][13][14][15][16][17][18] AlON, 19) ZrO 2 , 20,21) HfO 2 , 20,22) Si x N x -SiO 2 , 1) SiO 2 -HfO 2 , 8) Al 2 O 3 -HfO 2 , 23) and Al 2 O 3 -TiO 2 bilayers, 24) (Al, Si)O, 25) and Al 2 O 3 /SiO 2 laminate 26) (forming AlSiO x ) have been studied for use in MOS units, and films of these materials are typically deposited via chemical vapor deposition or atomic layer deposition (ALD). ALD is the optimal approach to fabricating conformal films on three-dimensional structures, which is required when producing vertical GaN devices.…”
mentioning
confidence: 99%
“…M.J. Zheng et al studied the effect of annealing on GaN-based semicon-ductor capacitors with ZrO 2 as dielectric layer prepared by atomic deposition method. The results showed that the capacitance gradually increased with the increase of annealing temperature from 300˚C to 500˚C [22]. A. Hosokawa et al…”
Section: Introductionmentioning
confidence: 95%